Shifting the focus of child and youth wellbeing programs from crisis to prevention: a mixed methods study of the role of First Nations’ community-controlled organisations - Janya McCalman; Merissa Nona; Mandy Edwards; Lucresia Willett; Ruth Fagan; Vicki Saunders; Alexandra van Beek; Sandy Campbell; Mary Anne Furst; Luis Salvador-Carulla (BMC Health Services Research)
Abstract Background Australian governments and the First Nations Coalition of Peaks, through the Closing the Gap reforms, have committed to build the Aboriginal and Torres Strait Islander community-controlled sector and increase decision making by community-controlled services. This paper describes a First Nations-led place-based research program with community-controlled health and youth service partners in Far North Queensland to understand and map the regional child and youth wellbeing service system and co-design strategies to improve service provision. Methods This mixed-method research was conducted through a First Nations-led approach that is both place-based and systems focused. Following research planning workshops with community-controlled health and youth service partners, 47 staff members from 27 Cairns and Yarrabah intersectoral child and youth-wellbeing organisations were interviewed in 2021-22 to map the characteristics of their services. Their responses were coded using a modified version of the internationally validated Description and Evaluation of Services and DirectoriEs for Long Term Care (DESDE-LTC) mapping tool to determine the characteristics of whole system intersectoral services. Forty-four participants then attended co-design workshops in each place to discuss the results and identify further priorities. Results A high 68% of the main types of care were crisis-related services (focused on child protection, youth justice, mental illness, homelessness, illness/injury, and disengagement from education), with just a third (32%) focused on prevention/early intervention. Despite clear leadership from community-controlled services, only 23% of the main types of care were delivered by community-controlled organisations, with 51% delivered by mainstream non-government organisations, and 26% by government departments. Funding agreements drove the characteristics of services, with community-controlled organisations providing a higher proportion of the more complex crisis-oriented services, whilst non-government organisations received funding for preventive programs. Service providers prioritised a need for greater investment in prevention and early intervention, with community control of decision making considered critical to improving the appropriateness of care. Conclusions These findings speak to the recent national commitment to increase decision making by Aboriginal and/or Torres Strait Islander community-controlled services. The recommendations of north Queensland regional service providers can inform improvements in the Closing the Gap reforms, and hence in the systems that support the wellbeing of First Nations children, youth and families.